Warm island effect observed in lake areas of the Badain Jaran Desert, China. (30th September 2021) - Zhao, Liqiang; Yu, Xinran; Zhang, Wenjia; Liang, Xiaoyan; Wang, Nai'ang; Cai, Wenjun
Abstract : Warm island effect was found in the lake region of Badain Jaran Desert, which challenged the past theory named cold island effect. To be specific, the lake region in winter underwent air temperature significantly higher than other regions of the desert. Warm island intensity is negatively correlated with solar radiation, while proportional to the lake area. And the warm island effect is mainly caused by the thermal storage of lakes in lake basins and the release of heat from deep groundwater.